Basic Stages of Energy Development Program Implementation in the Chechen Republic - Kerimov, I. A.; Mintsaev, M. Sh.; Debiev, M.V.; Pashaev, M. Ya. (International Journal of Energy Economics and Policy, 2020)
The article discusses the issues of energy complex development of the Chechen Republic, which requires the creation of a stable multi-vector energy that can satisfy the growing needs of the population and economy of the region. The main emphasis is made on the development of the renewable energy sources, which need to be paid close attention, drawing on the experience of other entities and countries developing innovative technologies in this direction. The analysis of the energy development program implementation in the Chechen Republic (2011-2030) over the past eight years has been carried out, which includes four subprograms describing the potential of resources and the prospects for the energy development in the Chechen Republic,. The estimation of power consumption indicators and maximum loads in the Chechen Republic until 2018 and for the long term (“calculated”, “optimistic” and “actual” options) is given. The analysis of the state and potential for the water energy development in the Chechen Republic is carried out. The analysis of natural resources potential of the republic is carried out in order to implement effectively and develop each of the considered renewable energy sources, taking into account the development of modern innovative technologies to reduce electrical energy consumption. The state estimation of the existing integrated power grid of the Chechen Republic is given, where the initial tasks of work coordination to improve the efficiency of the republic's energy system are outlined. The results of total indicators of electric grid construction and facilities reconstruction for 2011-2019 are derived. Possible directions (calculated and optimistic options) of the electrical energy industry development are considered. In order to develop successfully the energy sector of the Chechen Republic, taking into account the electrical energy load growth, the development of modern program for the of alternative and renewable energy sources development was proposed that will allow to create additional electrical energy sources in combination with traditional ones. At the same time, the implementation of fundamental and applied research in the field of renewable energy was proposed. Keywords: electric energy industry, power system, power center, electric energy, power balance, alternative and renewable energy sources. JEL Classifications: O13, P28, P48, Q42, Q43, Q47, R11 DOI: https://doi.org/10.32479/ijeep.10492